Effect of heat treatment on the tribological properties of Nickel-Boron electroless coating (2018)
ABSTRACT: Nickel-Boron autocatalytic coatings are widely used in several industries to improve mechanical properties of materials such as hardness and wear resistance. Tribological properties were evaluated in Ni-B autocatalytic coatings deposited on AISI/SAE 1018 carbon steel before and after a heat treatment at 450 °C for one hour. Tribological tests were carried out by dry sliding, using a load of 5 N and a sliding speed of 0.012 m/s, in a homemade ball-on-disk tribometer, which followed ASTM G99 standard. According to the tribological evaluation, the heat treatments applied to Ni-B coatings improved their tribological performance. This research corroborates that by applying an adequate heat treatment, hardness and wear resistance of Ni-B coatings can be improved significantly.